Pengembangan Perangkat Eksperimen Gerak Harmonik Sederhana untuk Pengamatan Trends dan Pemahaman Konseptual - Lanang Maulana Aminullah (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2026)
Apparatus capable of recording time-dependent data in experiments is essential for physics learning. In this study, we developed an experimental apparatus for Simple Harmonic Motion (SHM) on a spring to record time-dependent displacement. The development was carried out by integrating an HC-SR04 ultrasonic sensor into the basic design of the SHM experiment. The study shows that, from a visual observation perspective, instead of exhibiting simple harmonic motion represented by the waveform y=Acos(ωt), the oscillator displayed damped harmonic motion characterized by a gradually shifting phase, following the waveform equation y=Acos(ωt+ϕ(t)). Focusing on the technical validation of the apparatus, both visual representation and deviation analysis indicated that the developed experimental apparatus showed good agreement with the theoretical trend, with a Mean Absolute Error (MAE) of 0.9329. The apparatus demonstrated the capability to record meaningful qualitative trend data of simple harmonic motion to support analytical learning processes.